Compliance of Community Pharmacists and Private General Medical Practitioners With Malaysian Laws on Poisons and Sale of Drugs - Chuo, Yew Ting; Shing, Chyi Loo; Hiram, Ting; Wei, Chern Ang; Abu Hassan Alshaari, Abd Jabar (SAGE Publications Inc., 2017)
Background: Compliance of community pharmacists (CPs) and private general medical practitioners (GPs) with Malaysian Laws on Poisons and Sale of Drugs is crucial in encouraging rational supply of medicine to patients that will subsequently lead to rational use of medicine, especially controlled medicine and psychotropic substances. This study aims to identify the trend of yearly compliance rate of both CPs and GPs with the Malaysian Laws on Poisons and Sale of Drugs, and to quantify the effectiveness of disciplinary actions in improving their compliance level. Methods: This is a retrospective observation study from the Sarawak state Pharmaceutical Enforcement Division (PED) inspection reports on CPs and GPs from January 1, 2012, to December 31, 2014. Descriptive statistics in numbers and percentages are used to present the results. Results: From years 2012 to 2014, the compliance rate of GPs increased from 34% to 51%, while the compliance rate of CPs remained almost constant, with a slight drop from 53% (2012) to 50% (2014). The most common noncompliance found among CPs is with the Poison Acts 1952 Section 26 Condition 2: “Records for the supply of preparations containing Pseudoephedrine, Ephedrine and Dextromethorphan,” and among GPs, it is the Regulation 12 of Poisons Regulation 1952: “labeling of dispensed medicines.” Warning letter is the most effective disciplinary action for both CPs (75% improvement) and GPs (67.8% improvement). Conclusion: This study serves as a baseline that provides valuable insights to policy makers, researchers, and other stakeholders in developing better enforcement strategies. © 2017, ©The Author(s) 2016.